Design and implementation of a six-degree of freedom robotic platform for measuring the forces of flying objects - Banda, Richard (Department of Electrical Engineering, 2014)
The purpose of this project was to research, design and build a six-degree of freedom platform that measures the forces of flying animal robotics. The platform had to have an embedded force sensing mechanism and should be able to move in response to forces detected and measured. The platform had to measure the forces in six different orthogonal axes. The course of action and focus of the thesis was to research, design, build and control the robotic platform and it was an individual project.